2018
DOI: 10.1111/obes.12258
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in Educational Outcomes: How Important Is the Family?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 39 publications
5
18
1
Order By: Relevance
“…The literature on intergenerational mobility may overlook important components of family background by focusing on a single parental resource (Björklund & Jäntti, 2009; Bredtmann & Smith, 2018; Mazumder, 2008; Solon, 1999), that is, YP. Ultimately, what should be relevant for gauging equality of opportunity is whether health status is reproduced according to general family background, not the correlation of child health with one specific parental variable (i.e., parental health).…”
Section: Methodsmentioning
confidence: 99%
“…The literature on intergenerational mobility may overlook important components of family background by focusing on a single parental resource (Björklund & Jäntti, 2009; Bredtmann & Smith, 2018; Mazumder, 2008; Solon, 1999), that is, YP. Ultimately, what should be relevant for gauging equality of opportunity is whether health status is reproduced according to general family background, not the correlation of child health with one specific parental variable (i.e., parental health).…”
Section: Methodsmentioning
confidence: 99%
“…Björklund et al (2010) found an 18% reduction in the sibling correlation in income after controlling for father's occupation. Bredtmann and Smith (2016) show that controlling separately for mother's (father's) occupation decreases the sibling correlation in completing upper secondary education by 23% (21%). Hederos Eriksson et al (2016) study the different factors that could potentially explain why siblings are similar in terms of their criminal behaviour.…”
Section: Results For Parents' Risk Attitudesmentioning
confidence: 97%
“…Beyond this point, the psychic cost increases exponentially but the wage does not increase at the same rate. This outcome was complemented by others (Bredtmann & Smith, 2018;Savasci, & Tomul, 2013;Stromquist & Monkman, 2014) suggesting that a person gets an education based on its expected payout. There are other factors involved such as gender, average number of siblings and average income to needs ratio of the household; these factors do not increase the expected payout of education but they do influence the psychic cost of education (Bhopal, 2019;Chioda, 2016;Pervaiz & Akram, 2018).…”
Section: Some Researchersmentioning
confidence: 86%
“…This study proposed indicators such as the size of the household, age of the individual, gender of the individual, and income inequality in the family as possible determinants of educational inequality (Bredtmann & Smith, 2018). Since educational inequality may also lead to income inequality of the individual, this study used an instrumental GMM model to counter the endogeneity problem.…”
Section: Conclusion and Policy Implicationmentioning
confidence: 99%
See 1 more Smart Citation